The Influence of Loss Aversion, Herding Bias and Regret Aversion Towards Investment Decision to Shareholder in Pontianak - Equeza Ermulyawati; Dedi Hariyanto; Heni Safitri (Journal of Economics, Social, and Humanities, 2023)
Background: The purpose of this research is to know the influence of Loss Aversion, Herding Bias And Regret Aversion Towards Investment Decision to Shareholder in Pontianak. Method: The research method being used is associational research, with the use of classical assumption test, including normality test, multicollinearity test, and linearity test, meanwhile the statistical analysis used multiple linear regression analysis, analysis of correlation coefficient, coefficient of determination analysis, simultaneous test, partial test. Results: Based on the result of multiple linear regression analysis, it is estimated that the regression equation is Y= 6,741 + 0,446X1 + 0,026X2 + 0,366X3, the analysis of correlation coefficient values is 0,768 showed that the influence of Loss Aversion, Herding Bias and Regret Aversion towards Investment Decision is strong. Coefficient of determination showed that 50,1% of investment decision is influenced by Loss Aversion, Herding Bias and Regret Aversion and the other 40,9% influenced by another variable unstudied in this research. The result of F-test showed that Loss Aversion, Herding Bias and Regret Aversion significantly influenced investment decision. The T-test showed that Loss Aversion alone has had influenced towards investors’ investment decision. The T-test showed that Regret Aversion has had influence towards investors’ investment decision. Conclusion: There is influence of Loss Aversion, Herding Bias and Regret Aversion towards Investment Decision to Shareholder in Pontianak.